Students’ Perspective towards Arabic Class Based on Gender - Mufidah, Nuril; Hanini, Filza Aina (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
The grouping system of students in learning can effect on the learning process. This research used a descriptive qualitative method to describe the perspective of students of the Arabic Language Development Program (PKPBA) on the classifying system based on gender, which is divided into homogeneous classes (separate classes between students and college students) and heterogeneous classes (mixed classes of students). Data collection used observation of teaching and learning activities and interviews. The results of the study show a different perspective between men and women. Female students are more comfortable learning in homogeneous classes, especially beginner classes' so they are not ashamed to learn and practice Arabic even though their abilities are minimal. In contrast to the perspective of male students who are more comfortable in heterogeneous classes, they feel they can learn better. Learning feels vibrant and increases academic competitiveness because they are challenged to perform well in front of female students, including when practicing Arabic. To make students learn better and the ability to speak Arabic tends to increase.